Peculiarities of Pregnancy in Women with Different Body Mass - O. M. Nadvorna; O. D. Krugliachenko; Y. Y. Petrovsky (Kazimierz Wielki University, 2019)
The aim of the study is to identify the characteristics of pregnancy in women with different body mass before pregnancy on the background of extragenital diseases and to establish the risk groups to reduce the perinatal losses. Material and methods. Observations were conducted in the Odessa City Hospital № 5 specialized in preterm labour. We studied the cases of 134 pregnant women with burdened obstetric history on the background of anemia Stage I-II. There were women with the cardiovascular system disorders, pre-eclampsia. The average age of the surveyed women was 28.35.2 years old. The statistical data were collected using SPSS program. Results and discussion. Our study confirmed that the women who were overweight had by 12 % higher risk of occurrence of mild pre-eclampsia. In accordance with our research, one third of the women (32 %) were overweight hereditary, 14.9 % of the women had lack of body mass, which demonstrated high correlation with anemia during pregnancy. The overweight women as well as the women with lacking body mass form certain groups of risk. In the overweight women, mostly preeclampsia occurs, whereas the lack of body mass mostly causes such complications as anemia of I and II degrees. Conclusions. The identification and establishment of the risk groups among the overweight and underweight women is an appropriate method of prevention of the perinatal complications and losses.